A Statistical Empirical Model and RSM-Guided Isolation and Characterization of Cellulose from Invasive Weed Senna didymobotrya (Fresen.) Irwin & Barneby, through Chemical and Spectroscopic Techniques - Meseret Zebeaman Birhanu; Mesfin Getachew Tadesse; Rakesh Kumar Bachheti; Ibrahim Nasser Ahmed; Archana Bachheti (International Journal of Polymer Science)
Senna didymobotrya is one of the emerging invasive weeds in East and South Africa. One of the solutions for weed management involves isolating cellulose and converting it into valuable materials. In this research, the isolation of cellulose was optimized by the Plackett-Burman design (PBD) and response surface methodology using Box-Behnken design (BBD), both of which are statistical empirical models. The maximum isolated cellulose yield was 37.5% (w/w) using sulfuric acid 1.75% (w/v), sodium chlorite 3% (w/v) at pH of 3.5, and potassium hydroxide 6% (w/v) treatment. Each chemical treatment was done by heating the mixture at 90°C for 2 hrs. The cellulose yield obtained (37.5% (w/w)) was higher than the preoptimized value of 35.5% (w/w). The dewaxed powder of the weed, isolated cellulose, and commercial cellulose was characterized side by side for comparison using FTIR, XRD, SEM, and TGA/DTA. All the characterizing methods indicated that the isolated material was cellulose. Even though the intensity of FTIR and XRD graphs of the isolated cellulose was higher than the commercial cellulose, the crystallinity index calculated from XRD analysis showed that the commercial cellulose (83%) was higher than the isolated cellulose (78%). The TGA/DTA indicates that the isolated cellulose and commercial cellulose had comparable thermal stability, both stable at up to 360°C. Therefore, using this optimized method, cellulose isolation from S. didymobotrya opens avenues for converting cellulose into valuable materials like carboxymethyl cellulose, cellulose hydrogel, and cellulose nanocrystals.